Pembuatan Konten Sosialisasi Pencegahan Stunting pada Kader TPK Kec. Simpang menggunakan Aplikasi Canva - Dian Meilantika; salamudin salamudin; Sri Hartati; Rusidi Rusidi; Haris Saputro (Universitas Pahlawan Tuanku Tambusai, 2022)
This community service activity aims to make the cadres of the Family Assistance Team more innovative and take the initiative in socializing assistance to families at risk of Stunting. Stunting is malnutrition in infants in the first 1000 days of life that lasts a long time and causes inhibition of brain development and child growth and development. Due to chronic malnutrition, stunted babies grow shorter than the standard height of toddlers in their lifetime. With the socialization content of Stunting prevention on social media, TPK cadres can directly convey how to prevent Stunting from an early age to the wider community online. where nowadays couples of childbearing age and brides-to-be are more intense in using social media. This activity is carried out face-to-face with the demonstration method or direct practice using an android-based. This activity was carried out in collaboration with the Asian Mahakarya Asia University with the family planning counselling center of Simpang district. From this activity, the participants were able to create content for socializing Stunting prevention using the Canva application.